Management practices on strategic human resource towards employee performance through organizational commitment - Asa Azzukhruf, Rilantau Anggi; Noermijati, Noermijati; Rohman, Fatchur (Management and Entrepreneurship: Trends of Development, 2019)
Indonesia has entered international competition in regional sector due to the change on various business structures and behavior in globalization era. The international competition does not merely limit on the product competition but also on the human resource management. The enhancement on competition intensity has influenced the need escalation for organizations to keep improving their management organization performance, especially in human resource’s ability. It emphasized on the strategic approach which involved the relationship between company and its human resource management within the field of structure, culture and development. This study aimed to identify the influence of management practices on strategic human resource, including training selection, empowerments and performance appraisal, toward employee performance through organizational commitment. The methodology used in this study was quantitative methodology using survey questionnaire to the 145 employees of PT Petrokimia Gresik as the sample study. The findings of the study showed that management practices on strategic human resource had either direct or indirect positive influence towards the employee performance through organizational commitment. In conclusion, the organizational commitment and employee performance could be increase if the management practices on strategic human resource are good. Moreover, the enhancement of organizational commitment could affect the employee performance improvement. JEL Classification: L22, M54, P47.